Reflections on the potential of virtual citizen science platforms to address collective action challenges: Lessons and implications for future research. (1st November 2018) - Leeuwis, Cees; Cieslik, K.J.; Aarts, M.N.C.; Dewulf, A.R.P.J.; Ludwig, F.; Werners, S.E.; Struik, P.C.
Abstract: Rural communities in Africa are facing numerous challenges related to human health, agricultural production, water scarcity and service delivery. Addressing such challenges requires effective collective action and coordination among stakeholders, which often prove difficult to achieve. Against the background of the increased availability of information and communication technologies (ICTs), this article synthesizes the lessons from six case-studies reported in this Special Issue. The cases investigate the possible role of digital citizen science platforms (labelled EVOCAs: Environmental Virtual Observatories for Connective Action) in overcoming the challenges of integrating heterogeneous actors in collective management of common resources and/or the provision of public goods. Inspired by the seminal work of Elinor Ostrom, our expectation was that such platforms could help operationalize communication and information-related design principles and community conditions that are known to enhance the capacity to address environmental challenges. This article presents some cross-cutting insights and reflections regarding the nature of the challenges identified by the diagnostic studies, and on the relevance and significance of Ostrom's framework and analysis. It also reflects on the plausibility of our original ideas and assumptions by assessing what the various studies tell us about the significance and potential of key components of an EVOCA-type intervention: i.e. environmental monitoring, ICT, connective action, citizen science and responsible design. At the same time, we draw lessons for follow-up research and action in our research program and beyond by identifying several issues and themes that merit further investigation. Based on the case-studies, we conclude that many collective action challenges are of a more complex nature than originally anticipated, and often cannot be resolved within clearly demarcated communities. While this complicates the realization of Ostrom's communication and information-related design principles and community features, there may still be a meaningful role for digital citizen science platforms. To help address complex challenges, they must be oriented towards fostering adaptive and systemic learning across interdependent stakeholder communities, rather than focusing on the self-betterment of the communities alone. Such digital platforms need to be developed in a responsible manner that ensures complementarity with already existing patterns of communication and ICT-use, that anticipates dynamics of trust and distrust among interdependent stakeholders, and that prevents typical problems associated with the sharing of information such as privacy infringement and undesirable control over information by outsiders.